Travel motivations, preferences, and characteristics of women solo travelers in Bali - Putu Diah Sastri Pitanatri; Ni Wayan Giri Adnyani; Luh Putu Kartini; Marco Valeri (Journal of Applied Sciences in Travel and Hospitality, 2025)
This study explores solo women travelers in Bali, focusing on their travel motivations, preferences, and characteristics. The research aims to fill the gap in understanding how solo travel contributes to understanding women's travel in these popular destinations. The study focuses on Big Data analysis. Textual content from TripAdvisor reviews by solo woman travelers is analyzed using the BART Large Zero Shot model. This model classifies text according to Maslow's hierarchy of needs and Plog's psychographics model, identifying primary travel motivations and distinguishing between allocentric and psychocentric traveler types. The findings reveal that 36.39% of travelers are motivated by self-actualization, seeking personal growth and transformative experiences. Additionally, 83.79% of solo woman travelers prefer allocentric travel experiences, indicating a strong desire for adventure and cultural immersion. These results highlight the empowerment journey of solo woman travelers as they travel to new destinations independently. This research provides valuable insights into the empowerment of solo woman travelers, emphasizing the role of travel in fostering personal development and independence. By examining the specific motivations and preferences of these travelers, the study enriches the discourse on gender roles within modern tourism and offers a nuanced understanding of solo travel.